2015
DOI: 10.1016/j.bbamem.2014.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Membrane sorting via the extracellular matrix

Abstract: We consider the coupling between a membrane and the extracellular matrix. Computer simulations demonstrate that the latter coupling is able to sort lipids. It is assumed that membranes are elastic manifolds, and that this manifold is disrupted by the extracellular matrix. For a solid-supported membrane with an actin network on top, regions of positive curvature are induced below the actin fibers. A similar mechanism is conceivable by assuming that the proteins which connect the cytoskeleton to the membrane ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…115 It has been recently suggested that ECM proteins contribute to this lateral organization. 116 Signal integration between ECM-binding receptors (e.g., integrins) and extracellular signaling molecules is also know to vary based on ECM stratum. This has best been described for growth factor signaling and categorized as concomitant signaling, collaborative activation, direct activation, amplification, and negative regulation.…”
Section: Storage Presentation and Sensingmentioning
confidence: 99%
“…115 It has been recently suggested that ECM proteins contribute to this lateral organization. 116 Signal integration between ECM-binding receptors (e.g., integrins) and extracellular signaling molecules is also know to vary based on ECM stratum. This has best been described for growth factor signaling and categorized as concomitant signaling, collaborative activation, direct activation, amplification, and negative regulation.…”
Section: Storage Presentation and Sensingmentioning
confidence: 99%